MORPHOLOGICAL VARIATION OF KEDONDONG (SPONDIAS DULCIS PARKINSON) IN CENTRAL PART OF SUMATRA - Ibna Hayati; Alex Hartana; Nina Ratna Djuita; Nunik Sri Ariyanti (Floribunda, 2022)
Ibna Hayati, Alex Hartana, Nina Ratna Djuita & Nunik Sri Ariyanti. 2022. Morphological Variation of Kedondong  (Spondias dulcis Parkinson) in Central Part of  Sumatra. Floribunda 6(8): 315–323 — Kedondong (Spondias dulcis Parkinson), is widely cultivated in the tropics and reported possibly native plant from Malesia and Pacific. Since a long time several regions in Indonesia has been known as producing area. Around 60s, Sumatra has reputable kedondong from sabang which has sweet flavour and large size. However information on the morphological variation of kedondong germplasm is still limited. The objective of this study was to describe and grouped morphological variation of kedondong germplasm in central part of Sumatra. The specimens were explored and collected from Riau, West Sumatra, and Jambi. Fifty morphological characters were observed and scored for grouping analysis using UPGMA methods. Some characteristics of kedondong from central part of Sumatra are very varied. The kedondong specimens in the cluster analysis grouped into two main groups A and B based on the color of the mature fruit, but these characteristics may not qualify to be used as standard criteria for evaluating cultivated variety because within the group there are still variations in other characters, such as size and shape of the fruits. However based on fruit type, sweet kedondong tends to has oblong type.